BUILDING BETTER LAW: HOW DESIGN THINKING CAN HELP US BE BETTER LAWYERS, MEET NEW CHALLENGES, AND CREATE THE FUTURE OF LAW - Ursel, Susan (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2017)
The legal profession faces increasing challenges to the relevance, utility, and acceptance of law and the rule of law as tools of social organization that are important and essential to human beings. Often the issues which challenge law and legal systems seem perennial, obstinate, and intractable. In order to remain relevant to the societies it serves, the law needs to innovate. We need to find new ways of thinking about law as a human designed and deliberate system of social organization. In this context, adopting an innovation mindset is an important starting point. “Design thinking” offers us a description and practice of an innovation mindset that can be and is employed in a variety of professional contexts. This article is an introduction to design thinking, its challenges, and its possibilities for law. It postulates that in fact design thinking as a concept and as a set of techniques is particularly well suited for use in law, and that we actually employ many of its techniques already. The article argues that by bringing these techniques into sharper focus, we can both recognize how we are in some ways using them already, and more importantly, how they can be deployed in even more useful and innovative ways to “build better law” at all scales of the legal endeavour, from individual service to legal systems.